2018
DOI: 10.3168/jds.2018-14639
|View full text |Cite
|
Sign up to set email alerts
|

How electrodialysis configuration influences acid whey deacidification and membrane scaling

Abstract: With the rising popularity of Greek-style yogurts in the past few years, the production of acid whey has drastically increased. If sweet whey is usually further processed, the acid whey valorization comes with challenges because its drying is jeopardized by its high mineral and organic acid contents. For this reason, prior demineralization and deacidification are usually performed at industrial scale using a combination of ion exchange resins and electrodialysis. This whole process represents large amounts of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
48
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 34 publications
14
48
0
Order By: Relevance
“…In this case, the dissociated OH - ions of water will combine with Ca 2+ and Mg 2+ ions and will precipitate on the surface of cation exchange membranes. The substantial inorganic scaling fouling in the cation exchange membrane is consistent with numerous studies [ 41 , 42 , 43 , 44 ]. Cifuentes-Araya and co-authors [ 42 ] found that divalent cations precipitation with OH - ions produced by significant water splitting was reinforced by an important OH - leakage through CEM that highly alkalinized the membrane interfaces, and also counteracted the demineralization.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…In this case, the dissociated OH - ions of water will combine with Ca 2+ and Mg 2+ ions and will precipitate on the surface of cation exchange membranes. The substantial inorganic scaling fouling in the cation exchange membrane is consistent with numerous studies [ 41 , 42 , 43 , 44 ]. Cifuentes-Araya and co-authors [ 42 ] found that divalent cations precipitation with OH - ions produced by significant water splitting was reinforced by an important OH - leakage through CEM that highly alkalinized the membrane interfaces, and also counteracted the demineralization.…”
Section: Resultssupporting
confidence: 90%
“…In a previous study [ 43 ], the authors systematically investigated the fouling nature evolutions along with different ED trials, and they found that amorphous calcium carbonate appeared on cation exchange membrane due to intense water-splitting reaction. Dufton and co-authors [ 44 ] have studied the fouling of ED for acid via deacidification, and they found the calcite and brucite were identified on the cation exchange membrane. The high solution alkalinity by the water dissociation was the reason for the fouling.…”
Section: Resultsmentioning
confidence: 99%
“…The energy consumption of acid was determined by not only the stack resistance but also the concentration of H 2 SO 4 produced in the acid compartment, as shown in Equation (2). Thus, the higher energy consumption obtained in the BP-A-BP configuration resulted from the low conductivity of the H 2 SO 4 solution [32].…”
Section: Discussionmentioning
confidence: 99%
“…These phenomena are sufficiently covered in respective reviews (Suwal et al ; Mikhaylin and Bazinet ). The fouling issue is also known in EDBM applications (Wang et al ; Mikhaylin and Sion ; Haddad et al ; Dufton et al ; Merkel et al ). It is important that the electrogeneration plays a crucial role in fouling formation.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, several reports on EDBM application in acid whey treatment have emerged. Dufton et al () obtained acid whey with lowered content of lactic acid using conventional ED stack and one with bipolar membranes. Furthermore, Merkel et al () tested two alternative EDBM stacks in the processing of acid whey nanofiltration retentate.…”
Section: Introductionmentioning
confidence: 99%